CURRICULUM REFERS TO KKNI AT THE PGMI STUDY PROGRAM AT UIN RADEN FATAH PALEMBANG - Muhammad Dhori; Jonata; Ahmad Saufi Al Hadisi (Bajang Institute, 2021)
In accordance with PP No. 8 of 2012 and the Minister of Education and Culture of the Republic of Indonesia No. 73 of 2013 requires universities to implement a curriculum that refers to the IQF. In the PGMI study program, UIN Raden Fatah Palembang has implemented a curriculum system that refers to the KKNI. This study aims to determine the application of the curriculum referring to the KKNI in the PGMI study program of UIN Raden Fatah Palembang. The research method used in this study is a descriptive qualitative approach. Where in this study, researchers look for sources of descriptive data in the form of words or opinions from research subjects. Data collection was carried out by interview and observation methods. The analysis technique of data collection, presentation and conclusion. Data analysis was carried out on data collection and after all were collected. The results show that in general the KKNI curriculum has been implemented in the PGMI UIN Raden Fatah Palembang study program which is decent and good.